Hydrodynamic stability of multiphase reactors - Joshi, J.B; Deshpande, N.S; Dinkar, M; Phanikumar, D.V (Advances in Chemical Engineering, 2001)
Gas-liquid bubble columns, solid-liquid fluidized beds, gas-solid fluidized beds, gas-liquid-solid fluidized beds, and transport reactors are very widely used multiphase reactors. These reactors operate in either of the two characteristic regimes: particulate or homogeneous, and aggregative or heterogeneous. The rates of heat, mass, momentum transfer, and mixing are quite different in these two regimes. Therefore, it is important to know the range of operating and design parameters over which the two regimes prevail and the conditions under which the transition occurs. This subject has been extensively investigated during the past 50 years and numerous fundamental, semiempirical, and empirical approaches have been reported for the prediction of transition. All these studies have been analyzed in this monograph. Further, unified and generalized criteria have been developed. In view of these, the past published results have been discussed. Stability maps have been presented. For several multiphase reactors, comprehensive comparison has been presented between the predicted and the experimental conditions of transitions. The characteristic differences among the various multiphase systems have been brought out. Suggestions have been made for future work.